The serum level of sclerostin decreases in radiographic axial spondyloarthritis patients with fatty lesions - Xuegang Li; Haijian Jiang; Xu Wang; Shuping Zhong (Arthritis Research & Therapy)
Abstract Background Currently, the pathophysiology of new bone formation in radiographic axial spondyloarthritis (r-axSpA) remains unclear. Cellular elements and their secreted bone turnover markers might be one of the underlying mechanisms that drive the new bone formation. Our study aimed to investigate the role of bone turnover markers in r-axSpA patients with fatty lesions. Methods 73 r-axSpA patients were enrolled in this study. 48 and 25 patients were divided into r-axSpA group with and without fatty lesions. Clinical variables were collected and all patients received comprehensive rheumatologic assessment for disease activity, including Modified Stoke Ankylosing Spondylitis Spine Score (mSASSS), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Axial Spondyloarthritis Disease Activity Score (ASDAS). Fatty lesions in the sacroiliac joints (SIJs) were scored independently by two radiologists. Serum levels of bone turnover markers, including sclerostin, osteoprotegerin (OPG), procollagen I N-terminal propeptide (PINP), cross linked C-telopeptide of type I collagen (CTX-I), osteocalcin (OC), were measured using enzyme-linked immunosorbent assays. Results There were no significant differences between two groups in terms of gender, age, body mass index (BMI), duration, smoking, HLA-B27 positivity rate, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), BASDAI, ASDAS-ESR, ASDAS-CRP, biological disease-modifying anti-rheumatic drugs (bDMARDs) rate. No significant differences were observed in terms of OPG, PINP, CTX-I or OC between two groups. The mSASSS were higher in fatty lesions group than in those without fatty lesions (p < 0.001). The serum sclerostin levels were significantly lower in r-axSpA patients with fatty lesions than in those without fatty lesions (p < 0.001). There were correlations between BMI, mSASSS and sclerostin with the comprehensive Berlin scoring method (CBM) scores in the univariate analysis (ρ = 0.311, ρ = 0.306, ρ = -0.920, respectively). However, only sclerostin had correlation with the CBM scores in multivariate analysis (ρ = -0.040, p < 0.001). Conclusions In the r-axSpA patients with fatty lesions, serum sclerostin levels are declined. Serum sclerostin might be useful as a biomarker to predict the progression of the chronic inflammation in SIJs in r-axSpA.